Tracking the Literature of Tropical Weather
XI, 300 p. 2 illus. in color.
Keywords: This book tracks across history and cultures the ways in which writers have imagined cyclones, hurricanes, and typhoons, collectively understood as “tropical weather.” Historically, literature has drawn upon the natural world for its store of symbolic language and technical device, making use of violent storms in the form of plot, drama, trope, and image in order to highlight their relationship to the political, social, and psychological realms of human affairs. Charting this relationship through writers such as Joseph Conrad, Herman Melville, Gisèle Pineau, and other writers from places like Australia, Japan, Mauritius, the Caribbean, and the Philippines, this ground-breaking collection of essays illuminates the specificities of the ways local, national, and regional communities have made sense and even relied upon the literary to endure the devastation caused by deadly tropical weather.